Estudo da sobrecarga térmica em tendas para construção civil - Lauxen, Marcelo (Universidade do Vale do Rio dos Sinos, 2016)
This study aims to evaluate and verify the thermal efficiency of tents with and without thermal cover used in construction site through quantitative and comparatives evaluations, in order to verify the thermal conditions of human permanence in the interior/inside of this type of “building”. As a base for this study, a bibliography search was made to find information about the work environment, the influence of heat in it, the comfort, the thermal stress and how the human body behaves in environments with influence of heat, and what the Regulatory Standard NR 15 mentioned about the insalubrity by heat and how the heat index is determined by the IBUTG. With the obtained results, it is possible to verify the efficiency of the thermal tents, which while maintaining the working conditions within the limits of tolerance for the heat, on work in open air to enable the employer to increase productivity and punctuality in the delivery of the construction.
Keywords: Conforto térmico; Tendas; Construção civil; Produtividade; Thermal confort; Tent; Cicil construction; Productivity